PEMBELAJARAN ANAK BERKEBUTUHAN KHUSUS STUDI KASUS LEARNING DISORDER - Neela Afifah (Genderang Asa: Journal of Primary Education, 2022)
Learning for Children with Special Needs is a learning that is carried out by involving strategies, methods/techniques, evaluations and various learning media which have been varied according to the needs of students. The focus of this research is children with learning difficulties. The child in this case is a child who in carrying out ordinary activities is not as capable as children his age. Based on this, knowledge about children with learning disabilities is very important for educators, so that mishandling does not occur to them, either because of their inability to read, write, or count. The research method used is descriptive-qualitative method, with the research subjects are 9 students and 1 teacher of class V SDLBN Pelambuan West Banjarmasin. The object of research is the learning process of special needs children in that class. Data from observations, interviews, and documentation were analyzed to describe the results in the form of a conclusion. The results of this study indicate that in the fifth grade of the SDLBN, the learning objectives to be achieved for children with learning disabilities are not yet clear. This is because the existing learning does not specifically use planning or lesson plans for special needs children. The implementation of the learning carried out is quite supportive by involving the collaboration of strategies, methods, and various other educational media. Furthermore, the evaluation of learning used were in the form of multiple choice tests, and non-verbal and practical tests. This evaluation process has been quite well done by the teacher, and can help children practice the materials provided. Keywords: learning, children with special needs, learning disorders